PERANCANGAN ALAT PENGANGKAT SISTEM HIDROLIK TIPE H PADA TEMPAT PENCUCIAN MOBIL DENGAN KAPASITAS MAXIMUM 2,5 TON - MARSUDI MARSUDI; AMIR MARASABESSY; BAYU PERMANA; ERVINI MELADIYANI (JURNAL TEKNIK INDUSTRI, 2018)
Hydrolic system is tecknology wich uses fluid, work fluid that is used is oil with viscosity number of 10 SAE. This system work based on the principle of Pascal Low, that is if fluid given pressure, so that pressure will go to all direction by not added or less its pressure.By calculating of type H design hoistear system where as can be result teol that the permession strength of force material is bigger than the happenned strngth of force material.ߪ௕=9,25݇݃/݉݉ଶ. So that the construction of type H design hoist car system by using of material BJ 37 is said saved and strong to be used. On this type H design hoist car system based on SNI 05-3659-1995 which is about hydrolic fluid power with the rod end spherical eyes could be operated perfectly to hoist the car of 2,5 tonnes load. By desig specification of pump hydrolic capasity which is used 0,2 dm3/minutes, power of pump as big 5,4 KW and maximum of load capasity of 2,5 tonnes.Key word : Hydrolic system, type H design hoist, SNI